Developing standards framework for the zakat institution in Sudan - Maghrabi, Mahmoud Ghalib (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2022)
To date, poverty is still the most troubling affliction facing societies. In the Muslim world, the state of poverty is alarming. Despite the possession of wealth and vast natural resources, one third of the world’s poor reside in Muslim countries. Sudan is one of those Muslim countries that has yet to address its wide-spread poverty. Many poverty alleviation schemes have been adopted to reduce the severity of destitution, nevertheless this challenging task is yet to be accomplished. It is evident, in Islamic history, that Zakat institutions had tremendous success in eradicating poverty throughout Islamic civilizations. Nonetheless, due to the colonization and secularization of many Islamic countries under the western conquest, this institution was neglected and overlooked. However, the pressing need to tackle the affliction of poverty has brought life to this socio-economic instrument with the hope that it would be the answer to poverty in Muslim countries and the world at large. In spite of this revival, the current role of the Zakat institution faces many management constraints and challenges hampering its progress. Standards have been regarded as a benchmark for efficient management in many institutions, however very few studies have examined the potential of standards in enhancing the efficiency of Zakat Institutions. Regarding Sudan, there is a scarcity of literature investigating the challenges hindering the Zakat institution in Sudan. In addition, to the best of the researcher’s knowledge, there are hardly any studies that have developed standards framework to enhance the Zakat institution in Sudan. Therefore, the main objectives of the study are: to investigate the challenges facing the Zakat institution in Sudan as well as explore principles that would be essential to the development of a Zakat Standards Framework. Initially, a review of literature was conducted to propose principles of a Zakat Standards Framework, which were then investigated using a mixed method approach. The principles proposed were; Performance Assessment, Manpower Planning & Development, Transparency & Accountability, Evidence-based Decision -Making, Resource Optimization and Coordination & Collaboration. Qualitative data was collected via an interview with 12 Zakat experts in Sudan regarding the challenges facing Zakat institutions, in addition to investigating the status of the proposed principles of the Zakat Standards Framework. Quantitative data was collected via a survey questionnaire from 292 Zakat employees representing 21 administrative units in the Zakat Institution in order to validate and confirm the proposed principles as essential for the Zakat Standards Framework. Regarding, the first research objective, findings showed many internal and external challenges hindering the efficiency of the Zakat Institution from achieving its objectives. Findings of the second objective revealed that the Zakat Standards Framework comprised of the proposed principles would greatly help in enhancing the efficiency of the Zakat Institution in Sudan. Furthermore, the study highlighted many issues related to the status of each of the proposed principles as well as challenges that may arise in the implementation of the Zakat Standards Framework. Overall, the findings present a worthy contribution to Zakat literature in general and particularly in Sudan. It also provides practical implications to Zakat administrators, especially in Sudan.